2020
DOI: 10.1109/access.2020.3003351
|View full text |Cite
|
Sign up to set email alerts
|

CA-GAN: Class-Condition Attention GAN for Underwater Image Enhancement

Abstract: Underwater images suffer from serious color distortion and detail loss because of the wavelength-dependent light absorption and scattering, which seriously influences the subsequent underwater object detection and recognition. The latest methods for underwater image enhancement are based on deep models, which focus on finding a mapping function from the underwater image subspace to a ground-truth image subspace. They neglect the diversity of underwater conditions which leads to different background colors of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Deep learning was gradually emerging and applied in various fields, and underwater image enhancement [41]- [43] is no exception. Perez et al [41] used a convolutional neural network (CNN) for image enhancement for the first time.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep learning was gradually emerging and applied in various fields, and underwater image enhancement [41]- [43] is no exception. Perez et al [41] used a convolutional neural network (CNN) for image enhancement for the first time.…”
Section: Related Workmentioning
confidence: 99%
“…Zong et al [42] proposed an enhancement algorithm based on CycleGAN to enhance the robustness and adaptability of the network. Wang et al [43] suggested using the CA-GAN method for image enhancement. First, underwater degraded images with different attenuation coefficients and depths are synthesized according to the physical model, and then CA-GAN is used to create a manyto-one mapping function, and an attention mechanism is also introduced to improve the visual effect of the image.…”
Section: Related Workmentioning
confidence: 99%
“…Guo et al [44] improved the quality of underwater images by a multi-scale dense generative adversarial network. Other relevant works of data-driven UIE methods can be found in [45], [46], [47].…”
Section: A Underwater Image Enhancementmentioning
confidence: 99%
“…Since its introduction in 2014, GAN [17] continues to attract growing interests in the deep learning community and has been applied to various domains such as computer vision [28]- [33], natural language processing [34], [35], time series synthesis [36], [37], and semantic segmentation [38], [39]. Specifically, GAN has shown significant recent success in the field of computer vision on a variety of tasks such as image generation [28], [29], image to image translation [30], [31], and image super-resolution [32], [33]. The standard GAN structure comprises two neural networks: a generator G and a discriminator D which are iteratively trained by competing against each other in a minimax game, where the generator attempts to produce realistic samples while the discriminator attempts to distinguish the fake samples from the real ones.…”
Section: A Generative Adversarial Networkmentioning
confidence: 99%